2013
DOI: 10.1186/1751-0759-7-1
|View full text |Cite
|
Sign up to set email alerts
|

The alexithymic brain: the neural pathways linking alexithymia to physical disorders

Abstract: Alexithymia is a personality trait characterized by difficulties in identifying and describing feelings and is associated with psychiatric and psychosomatic disorders. The mechanisms underlying the link between emotional dysregulation and psychosomatic disorders are unclear. Recent progress in neuroimaging has provided important information regarding emotional experience in alexithymia. We have conducted three brain imaging studies on alexithymia, which we describe herein. This article considers the role of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
99
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(113 citation statements)
references
References 91 publications
(125 reference statements)
5
99
1
8
Order By: Relevance
“…A high prevalence of alexithymia has been observed in patients with chronic pain (9), including those with RA (14,15). Numerous observational and some experimental studies revealed positive associations between alexithymia and pain intensity and sensitivity (16). However, there are some conflicting reports; alexithymia has been suggested to be associated with poor awareness of physical symptoms, such as cardiac pain, resulting in a delay of seeking treatment (17).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…A high prevalence of alexithymia has been observed in patients with chronic pain (9), including those with RA (14,15). Numerous observational and some experimental studies revealed positive associations between alexithymia and pain intensity and sensitivity (16). However, there are some conflicting reports; alexithymia has been suggested to be associated with poor awareness of physical symptoms, such as cardiac pain, resulting in a delay of seeking treatment (17).…”
Section: Introductionmentioning
confidence: 95%
“…Another shortcoming of previous studies is that most of them evaluated the output of pain without considering the inputs of pain (13). According to recent experimental studies, those with alexithymia may be insensitive to their own physical sensation when the external stimuli are not strong enough (16,20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with Lane [10], Kano and Fukudo [11] found evidence by reviewing brain imaging studies, that people who have deficits in the cognitive experience of emotions only experience rudimentary forms of emotional experience (high arousal of bodily sensations) and this may lead to disadaptive behaviours.…”
Section: Introductionmentioning
confidence: 89%
“…The present study however suggests that somatoform patients do report anxiety to a similar extent as other psychiatric patients do. Their anxiety may be related to an anxious preoccupation with illness symptoms [11].…”
Section: Discussionmentioning
confidence: 99%